Daily steps and all-cause mortality: a meta-analysis of 15 international cohorts - Paluch, Amanda E; Bajpai, Shivangi; Bassett, David R; Carnethon, Mercedes R; Ekelund, Ulf; Evenson, Kelly R; Galuska, Deborah A; Jefferis, Barbara J; Kraus, William E; Lee, I-Min; Matthews, Charles E; Omura, John D; et al. (The Lancet. Public health, 2022)
Although 10 000 steps per day is widely promoted to have health benefits, there is little evidence to support this recommendation. We aimed to determine the association between number of steps per day and stepping rate with all-cause mortality. In this meta-analysis, we identified studies investigating the effect of daily step count on all-cause mortality in adults (aged ≥18 years), via a previously published systematic review and expert knowledge of the field. We asked participating study investigators to process their participant-level data following a standardised protocol. The primary outcome was all-cause mortality collected from death certificates and country registries. We analysed the dose–response association of steps per day and stepping rate with all-cause mortality. We did Cox proportional hazards regression analyses using study-specific quartiles of steps per day and calculated hazard ratios (HRs) with inverse-variance weighted random effects models. We identified 15 studies, of which seven were published and eight were unpublished, with study start dates between 1999 and 2018. The total sample included 47 471 adults, among whom there were 3013 deaths (10·1 per 1000 participant-years) over a median follow-up of 7·1 years ([IQR 4·3–9·9]; total sum of follow-up across studies was 297 837 person-years). Quartile median steps per day were 3553 for quartile 1, 5801 for quartile 2, 7842 for quartile 3, and 10 901 for quartile 4. Compared with the lowest quartile, the adjusted HR for all-cause mortality was 0·60 (95% CI 0·51–0·71) for quartile 2, 0·55 (0·49–0·62) for quartile 3, and 0·47 (0·39–0·57) for quartile 4. Restricted cubic splines showed progressively decreasing risk of mortality among adults aged 60 years and older with increasing number of steps per day until 6000–8000 steps per day and among adults younger than 60 years until 8000–10 000 steps per day. Adjusting for number of steps per day, comparing quartile 1 with quartile 4, the association between higher stepping rates and mortality was attenuated but remained significant for a peak of 30 min (HR 0·67 [95% CI 0·56–0·83]) and a peak of 60 min (0·67 [0·50–0·90]), but not significant for time (min per day) spent walking at 40 steps per min or faster (1·12 [0·96–1·32]) and 100 steps per min or faster (0·86 [0·58–1·28]). Taking more steps per day was associated with a progressively lower risk of all-cause mortality, up to a level that varied by age. The findings from this meta-analysis can be used to inform step guidelines for public health promotion of physical activity. US Centers for Disease Control and Prevention.